Second language learner engagement in computer-mediated interactive oral tasks - Qiu, Xuyan; Lo, Yuen Yi; Ge, Haoyan; Bui, Gavin (Studies in Second Language Learning and Teaching, 2025)
This study investigated the engagement of 60 Hong Kong English-as-a-second-language (ESL) learners in two types of tasks, each with two levels of complexity (-elements/simple versus +elements/complex). The learners formed self-initiated pairs and completed two descriptive tasks (-reasoning demand) and two narrative tasks (+reasoning demand) in a counterbalanced order in synchronous video-based computer-mediated communication (SvCMC) across two separate meetings. Immediately after each task performance, the learners were interviewed about their emotional experiences during the tasks. Quantitative analysis of their spoken discourse revealed that learners were more cognitively engaged in the simple descriptive task than in the complex one. However, the number of elements did not seem to affect learner engagement in the narrative tasks. Descriptive tasks engaged learners behaviorally in task performance, while narrative tasks encouraged social engagement. The participants generally found both types of tasks emotionally engaging, but more participants experienced positive emotions during the descriptive tasks than during the narrative tasks. These findings suggest that task complexity and task type should be carefully considered when designing interactive oral tasks in online teaching and learning contexts.